Sustained censorship in OM (2026-05) (Oman) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Oman. Data sourced from OONI.
Censorship Incident ID: OM-2026-0191. Severity: critical. Confidence: 85%